Research on redundant structure of cloud-based interlocking systems - HE Zhibin; XING Kejia; LIANG Zhiguo; WEI Dongdong; ZHENG Changzong (机车电传动)
In order to ensure the operational safety of interlocking systems within cloud platforms, this paper presented a redundant structure for cloud-based interlocking systems based on virtual machine fault tolerance technology, through analyzing the redundant structure of the existing computer-based interlocking systems and considering the characteristics of cloud platforms. Firstly, the characteristics and advantages of the redundant structure of cloud-based interlocking systems were elaborated. Subsequently, this paper analyzed the working mode and server failure factors, and established a server fault tree model and dynamic fault tree model to evaluate the probability of failure on danger (PFD) and probability of failure to safety (PFS). Finally, the reliability of the redundant structure of cloud-based interlocking systems was assessed by simulation analysis using the dynamic fault tree model. The results indicate that cloud platforms are more suitable for deploying interlocking systems in multiple redundant structures such as MooN structures. This research on the redundant structure for cloud-based interlocking holds certain reference significance for the development of cloud-based interlocking systems.